Relative analysis of the dependency of spectrophotometric data on temperature using textiles, ceramics, plastics, paints, and printed materials. Issue 6 (24th October 2018) - Che, Jiangning
Abstract: It is generally known that the color of an object changes with the change of its surface temperature. The purpose of this study is to investigate the relative dependency of measured colorimetric data on the temperature variation of an object for different types of colored materials. Specifically, textile fabrics, ceramic tiles, plastic plaques, ink‐printed paper cards, and paint‐coated cards were utilized, and the results were evaluated. The impacts of temperature alteration on the CIELAB colorimetric data were examined and evaluated. The total color difference and differences in the CIE coordinates of each colored sample, compared with the measured color data at 20°C, are presented. The results reveal how each measured CIE colorimetric coordinate, as well as color difference, varies with the surface temperature of the object for samples of different types of colored materials.